Functional and immunological relationships between metyrapone reductase from mouse liver microsomes and 3 alpha-hydroxysteroid dehydrogenase from Pseudomonas testosteroni. - Maser, E; Oppermann, U; Bannenberg, G; Netter, K (1992)
3 Alpha-hydroxysteroid dehydrogenase (3 alpha-HSD) from Pseudomonas testosteroni was shown to reduce the xenobiotic carbonyl compound metyrapone (MPON). Reversely, MPON reductase purified from mouse liver microsomes and previously characterized as aldehyde reductase, was competitively inhibited by 3 alpha-HSD steroid substrates. For MPON reduction both enzymes can use either NADH or NADPH as co-substrate. Immunoblot analysis after native and SDS gel electrophoresis of 3 alpha-HSD gave a specific crossreaction with the antibodies against the microsomal mouse liver MPON reductase pointing to structural homologies between these enzymes. In conclusion, there seem to exist structural as well as functional relationships between a mammalian liver aldehyde reductase and prokaryotic 3 alpha-HSD. Moreover, based on the molecular weights and the co-substrate specificities microsomal mouse liver MPON reductase and Pseudomonas 3 alpha-HSD seem to be members of the short-chain alcohol dehydrogenase family.